Macelignan protects against renal ischemia-reperfusion injury via inhibition of inflammation and apoptosis of renal epithelial cells - Long, Jianhua; Qian, Kun; Tan, Shubo; Liu, Jia; Li, Jianjun (Cellular and Molecular Biology, 2020)
Ischemia-reperfusion injury (IRI) refers to tissue damage that occurs when blood supply returns to tissue after a period of ischemia, anoxia or hypoxia. It occurs frequently during shock, organ transplantation and heart failure. It can cause impairment or even renal failure. Macelignan is a lignin isolated from the seeds of Myristica fragrans. It has been reported to inhibit neuroinflammation and oxidative toxicity. The preventive or therapeutic effects of macelignan on renal IRI has not been reported. The present study investigated the effects of macelignan on renal IRI in rats, and the underlying mechanism(s). Healthy adult male Sprague Dawley rats (n = 50) aged 7 – 9 weeks (mean weight = 220 ± 20 g) were used in this study. The rats were randomly assigned to five groups of 10 rats each: sham treated group, IRI group and 40 mg macelignan/kg body weight (bwt) group, 80 mg macelignan/kg bwt group, and 160 mg macelignan/kg bwt group. Ischemia-reperfusion injury was induced in the rats using standard procedure. The results showed that serum levels of creatinine, blood urea nitrogen (BUN), interleukin-6 (IL-6), tumor necrosis factor Î± (TNF-Î±) and gamma interferon (IFN-Î³) were significantly higher in IRI group than in sham treated group, but were significantly and dose-dependently reduced after treatment with macelignan (p < 0.05). The activities of catalase and superoxide dismutase (SOD), and reduced glutathione (GSH) level were significantly reduced in IRI group, when compared with sham treated group, but were significantly and dose-dependently increased after treatment with macelignan (p < 0.05). However, the level of malondialdehyde (MDA) was significantly higher in IRI group than in sham treated group, but treatment with macelignan reduced it significantly and dose-dependently (p < 0.05). Macelignan also significantly and dose-dependently inhibited IRI-induced apoptosis in epithelial cells of renal tubules (p < 0.05). The results of Western blotting showed that IRI significantly upregulated the expressions of bax and caspase-3, and down-regulated the expression of bcl-2 in epithelial cells of renal tubules (p < 0.05). However, treatment with macelignan significantly and dose-dependently down-regulated the expressions of bax and caspase-3 in these cells, but significantly and dose-dependently upregulated the expression of bcl-2. These results show that macelignan confers protection on renal IRI via mechanisms involving inhibition of inflammation and apoptosis, and stimulation of natural antioxidant defense system.